Platelet-rich plasma ultrasound-guided injection in the treatment of carpal tunnel syndrome: A placebo-controlled clinical study. - Malahias, Michael-Alexander; Nikolaou, Vasileios S; Johnson, Elizabeth O; Kaseta, Maria-Kyriaki; Kazas, Sotirios-Tsambikos; Babis, George C (J Tissue Eng Regen Med, 2018)
The purpose of this study is to demonstrate whether and to what extent a single injection of platelet-rich plasma (PRP), under ultrasound guidance, can improve the clinical symptoms of patients with a mild to moderate carpal tunnel syndrome (CTS). We conducted a prospective, randomized, clinical study including 50 patients suffering from mild to moderate CTS for a minimum duration of 3 months. Patients were randomly divided into 2 groups: Group A (26 patients) received an ultrasound-guided PRP injection into the carpal tunnel, whereas Group B (24 patients) was injected with placebo (0.9% normal saline). The short- and mid-term outcomes were determined with the use of the Q-DASH questionnaire and the pain scale VAS administered at 0, 4, and 12 weeks follow-up. The success ratio was determined by the difference in the Q-DASH obtained pre-injection minus the final Q-DASH obtained after 12 weeks follow-up. Success was defined as a difference more than 25%. Group A patients demonstrated a 76.9% success as determined by the difference Q-DASH, whereas Group B patients demonstrated 33.3% success, which was significantly less than Group A (Χ , p = .011). The findings of this study suggest that a single PRP ultrasound-guided injection has positive effects in patients with CTS.